Innovative Marketing Strategic to Improve Business Growth at PT Dialogika Persona Indonesia: - - Alfa Yudishtira; Albari, Albari (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the innovative marketing strategies implemented by PT Dialogika Persona Indonesia, a training service company specializing in public speaking and personal development, to enhance business growth and engagement through digital technology. The research adopts a qualitative method with descriptive analysis based on the company's internal data, including Google Analytics, ClickUp, and social media platforms such as Instagram and TikTok. This study also involves in-depth interviews regarding the marketing strategies utilized by the company as well as the innovations that have been prepared. The findings reveal that PT Dialogika Persona Indonesia implements various marketing and supporting strategies to market and promote its services. The company has also prepared new innovations to improve brand awareness, engagement, sales, business growth, and to achieve its vision of becoming the most comfortable platform for individuals to develop themselves.